2021
DOI: 10.7150/thno.56604
|View full text |Cite
|
Sign up to set email alerts
|

MYBL2 disrupts the Hippo-YAP pathway and confers castration resistance and metastatic potential in prostate cancer

Abstract: Rationale: Resistance to androgen-deprivation therapy (ADT) associated with metastatic progression remains a challenging clinical task in prostate cancer (PCa) treatment. Current targeted therapies for castration-resistant prostate cancer (CRPC) are not durable. The exact molecular mechanisms mediating resistance to castration therapy that lead to CRPC progression remain obscure. Methods: The expression of MYB proto-oncogene like 2 (MYBL2) was evaluated in PCa samples. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…The expression of MYBL2 gene is controlled by other transcription factors or noncoding RNA (41)(42)(43)(44)(45), and the MYBL2 protein is activated via phosphorylation (14,21). After activated, MYBL2 regulates downstream diverse genes or proteins involved in multiple cellular processes, such as BCL2 and MYC in cell survival (46)(47)(48), cyclins and FGF4 in cell cycle (49-51), SOX2 and OCT4 in cell differentiation (52,53), SNAIL and YAP1 in cell invasion and metastasis (19,54). Overexpression or amplification of MYBL2 had been widely reported in previous studies on cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of MYBL2 gene is controlled by other transcription factors or noncoding RNA (41)(42)(43)(44)(45), and the MYBL2 protein is activated via phosphorylation (14,21). After activated, MYBL2 regulates downstream diverse genes or proteins involved in multiple cellular processes, such as BCL2 and MYC in cell survival (46)(47)(48), cyclins and FGF4 in cell cycle (49-51), SOX2 and OCT4 in cell differentiation (52,53), SNAIL and YAP1 in cell invasion and metastasis (19,54). Overexpression or amplification of MYBL2 had been widely reported in previous studies on cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression or amplification of MYBL2 had been widely reported in previous studies on cancer. For instance, MYBL2 was overexpressed in castration-resistant prostate cancer and promoted cell growth and metastatic by promoting YAP1 transcriptional activity (19). Liang et al reported that MYBL2 expression was increased in gallbladder cancer and could serve as a potential prognostic biomarker (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYBL2, another significantly upregulated gene in the altered group, is a member of MYB transcription family and a positive regulator of the cell cycle which binds to the promoter of G2/M phase genes, such as CCNB1, CDK1, CCNA2, BCL2, and BIRC5 [89,90]. Over-expression of MYBL2 is defined in several cancers such as breast [91] lung [92], esophagus [93], colorectal [94], bladder [95] and prostate [96] cancers. BIRC5 is a well-characterized anti-apoptotic gene playing a role in the presentation of apoptosis, and our results described it as one of the top upregulated genes in the altered group compared to the unaltered samples.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described previously (Li et al, 2021). The following primary antibodies were used in this study: anti-p53 wild-type (clone PAb1620 (Puca et al, 2008); Merck Millipore, Billerica, MA, USA), anti-CXCR4 (ab124824; Abcam, Cambridge, United Kingdom), anti-AIP4 (NBP2-55083; Novus Biologicals, Littleton, CO, USA), anti-α-tubulin (T9026; Sigma-Aldrich), and anti-GAPDH (#97166; Cell Signaling Technology, Danvers, MA, USA) antibodies.…”
Section: Western Blot Analysismentioning
confidence: 99%